1984
DOI: 10.1111/j.1365-2125.1984.tb02367.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of prednisone and its metabolite prednisolone in children with nephrotic syndrome during the active phase and in remission.

Abstract: 1 The kinetics at steady state of prednisone and its metabolite prednisolone were determined in nine nephrotic children during the active phase of the disease and in remission. 2 There were no differences in serum prednisone levels between the two occasions. Prednisone levels were lower than prednisolone levels. 3 Total serum prednisolone levels were significantly lower during the active phase than in remission (AUC: 2452 ± 207 vs 3392 ± 293 ng ml-' h respectively). Half-life values were similar on both occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
10
0
3
Order By: Relevance
“…Studies performed in children with nephrotic syndrome demonstrated that prednisolone PK parameters did not correlate with clinical effectiveness 8 and that PK is unlikely associated with steroid unresponsiveness in children with nephrotic syndrome. 26 Another study performed in children with steroid-dependent asthma showed that the PK of prednisolone (administered intravenously in this study) is unrelated to patients’ clinical response to therapy. 27 …”
Section: Discussionmentioning
confidence: 64%
“…Studies performed in children with nephrotic syndrome demonstrated that prednisolone PK parameters did not correlate with clinical effectiveness 8 and that PK is unlikely associated with steroid unresponsiveness in children with nephrotic syndrome. 26 Another study performed in children with steroid-dependent asthma showed that the PK of prednisolone (administered intravenously in this study) is unrelated to patients’ clinical response to therapy. 27 …”
Section: Discussionmentioning
confidence: 64%
“…This reduced protein binding may also give rise to accelerated overall clearance of the drug. These two potential mechanisms often offset each other and render the influence of hypoalbuminemia on the pharmacokinetics negligible [36][37][38].…”
Section: Discussionmentioning
confidence: 96%
“…Certain drugs which interfere at the cellular transporter level, such as diltiazem, are capable of inhibiting P-gp function and increasing systemic prednisolone exposure and its antilymphocytic effects [23]. Nevertheless, previous studies carried out in nephrotic children showed no apparent correlation between the concentration-time profile of prednisone or prednisolone administered orally in a commercially available form and treatment outcome in terms of relapse rate [24,25]. To our knowledge, there are no clinical studies addressing the role of P-gp in prednisone/prednisolone absorption or excretion.…”
Section: Discussionmentioning
confidence: 97%